Sand and Dust Storms in Uzbekistan: Atmospheric Modeling for Understanding Impacts and Mitigation - Akramkhanov, Akmal; Haddad, Mira; Patlakas, Platon; Umarov, Sherzod; Nurbekov, Aziz; Yazici, Ekrem (International Center for Agricultural Research in the Dry Areas, 2024)
This report investigates the challenges posed by sand and dust storms (SDS) in Uzbekistan and explores mitigation strategies using an atmospheric modeling approach.